“… but he stayed up reading”: Books, Readers, and Reading in an Eighteenth‑Century East Norwegian Parish - Lishaugen, Roar (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2022)
With an ambition to add new knowledge on early modern reading culture in rural Norway, this essay zooms in on an eighteenth-century East Norwegian parish and conducts a detailed examination of various sources (church records, probate records, auction records, court records) to investigate how reading came into being and took place. Besides supporting previous conclusions about a widespread Scandinavian early modern rural literacy and a preponderance of religious books as owned, sold and bought by the rural population, the essay identifies a rural interest in books far exceeding the religious domain and an attraction to the materiality of books beyond reading. Moreover, court records disclose attitudes and practices related to reading and offer a promising avenue for generating further insights about how and why reading happened.